Improving Pepper Inbreds for Resistance to Pepper Yellow Leaf Curl Thailand Virus (PepYLCTHV) through Challenged Inoculations - Nattika Kumsee; Patcharaporn Suwor; Montinee Teerarak; W. S. Tsai; Suchila Techawongstien; Tanyarat Tarinta; Sanjeet Kumar; Nakarin Jeeatid; Orawan Chatchawankanphanich; Somsak Kramchote (Horticulturae, 2024)
Chili peppers (Capsicum annuum L.) are an economically important crop worldwide. Pepper yellow leaf curl Thailand virus (PepYLCTHV), a Begomovirus causing yellow leaf mosaic disease of chili pepper, has been reported to incur 95% economic loss under epiphytotic conditions. Thirty-one chili genotypes were screened for resistance to PepYLCTHV disease through inoculation using 10–15 viruliferous whiteflies per plant. We purified two resistant lines (PEP6 and PEP12) through four generations of selfing and selection. At 28 days after inoculations, two chili genotypes (PEP6 and PEP12) had low disease severity and percentage of disease incidence (DI) compared to four susceptible checks, viz., Yodsonkeam80, Homsupan, Huareau12, and Pong Charian, which had a disease severity score of 5 with 100% DI. Thirty initial plants of PEP6 showed an average disease severity of 3.64 with 69.33% DI, and PEP12 showed an average disease severity of 3.83 with 77.67% DI. From these populations, we selected nine highly resistant plant of PEP6 and seven plants of PEP12 having a disease severity of 0 through pure-line selection for four selfing generations. The ratio of resistance (R) to susceptibility (S) consequently decreased. In PEP6, the ratio decreased from 1R:2S to 1R:1S, while in PEP12 the ratio decreased from 1R:3S to 1R:1S. These lines have potential for release as resistant lines for improving chili pepper resistance to PepYLCTHV and for developing makers associated with the resistant trait.
Keywords: Plant Virus Research Studies; Agricultural pest management studies; Genetic and Environmental Crop Studies